2007
DOI: 10.1002/adma.200701747
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Neuronal Responses by Controlled Integration of Acetylcholine‐like Functionalities in Biomimetic Polymers

Abstract: This paper describes a new pathway to neuroactive materials that relies on integration of neurotransmitter‐like functional groups into synthetic polymers. A series of biodegradable polymers are synthesized with varying concentrations of acetylcholine‐like functionalities (ALFs) using a modular design. The polymers with medium ALF contents resemble laminin in promoting neurite sprouting and extension while maintaining phenotypic protein expression of neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 35 publications
3
38
0
Order By: Relevance
“…Due to the high reactivity of the epoxide groups, our preliminary attempts, including Tl(OAc) 3 -catalyzed transesterification, DCC/DMAP-mediated condensation, and the reaction between sodium sebacate and epichlorohydrin [35], led to complex reaction mixture and very low yields, and were therefore considered to be failures. Later, we prepared diglycidyl sebacate by epoxidation of diallyl sebacate, which was prepared via esterification of allyl alcohol and sebacic acid [33]. The yield was only approximately 60%, however, despite attempts to vary conditions such as reaction temperature, reaction time, and reactant ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high reactivity of the epoxide groups, our preliminary attempts, including Tl(OAc) 3 -catalyzed transesterification, DCC/DMAP-mediated condensation, and the reaction between sodium sebacate and epichlorohydrin [35], led to complex reaction mixture and very low yields, and were therefore considered to be failures. Later, we prepared diglycidyl sebacate by epoxidation of diallyl sebacate, which was prepared via esterification of allyl alcohol and sebacic acid [33]. The yield was only approximately 60%, however, despite attempts to vary conditions such as reaction temperature, reaction time, and reactant ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Glycerol-based polyesters prepared using direct chemical (Scheme 1) or lipase-catalyzed polycondensation are usually compromised by premature crosslinking, large polydispersity index (PDI), or low molecular weight [1, 30, 31]. We recently reported the application of epoxide ring-opening polymerization between biomolecules with primary amines and diglycidyl esters that led to polymers with free -OH groups [32, 33]. We reasoned that a similar polymerization between a diacid and a diglycidyl ester would produce a useful PSeD polyester (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For example, synthetic elastomers may also benefit from incorporating bioactive small molecules into the bulk material. [121] The utilization of naturally occurring molecules as monomers is compatible with established synthesis and processing techniques and could have substantial impact on improving the degree of cell-biomaterial interaction in tissue engineering scaffolds. Incorporating electronic and photonic capabilities within biodegradable elastomers may also be explored through careful monomer selection and efficient synthetic routes.…”
Section: Resultsmentioning
confidence: 99%
“…The polymer surface prepared with 1:60 (mol/mol) of MePEG-GMA to DMAEMA induced neuronal growth response similar to that on poly-L-lysine. Christiane et al [37] have also incorporated ACh-like functionalities (ALFs) in a series of linear polymers based on diglycidylsebacate, leucine ethyl ester, and aminoethyl acetate. The polymers were also coated onto glass coverslips, and results showed that ALFs had a profound impact on sprouting and neurite extension of dorsal root ganglia (DRG) cells in a concentration-dependent manner, the polymer with 70% ALF induced regenerative responses similar to laminin.…”
Section: Discussionmentioning
confidence: 99%